HUBUNGAN MOTIVASI BELAJAR DAN PROKRASTINASI PADA SISWA KELAS VIII SMPN 2 KADUNGORA KABUPATEN GARUT - Eros Sundaroh; Teti Sobari; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
The purpose of this study was to determine whether there was a relationship between academic procrastination and student learning motivation grade VIII  SMPN 2 Kadungora Kabupaten Garut. The sampling technique was used a purposive sampling technique to obtain a research sample of 56 people. The research method uses a quantitative correlational design approach with product moment correlation data analysis techniques based on questionnaire data with scale learning motivation and student learning independence. Data analysis use the application of SPSS 22 with a analys correlation value of 0.348  meaning  that there was a significant relationship between academic procrastination and learning motivation of Grade VIII  SMPN 2 Kadungora Kabupaten Garut Keywords: Academic Procrastination, Learning Motivation